2006
DOI: 10.1093/nar/gkl466
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of local DNA conformation by the human papillomavirus type 6 E2 protein

Abstract: The E2 proteins are transcription/replication factors from papillomaviruses. Human papillomaviruses (HPVs) can be broadly divided in two groups; low-risk HPV subtypes cause benign warts while high-risk HPVs give rise to cervical cancer. Although a range of crystal structures of E2 DNA-binding domains (DBD) from both high- and low-risk HPV subtypes have been reported previously, structures of E2 DBD:DNA complexes have only been available for high-risk HPV18 and bovine papillomavirus (BPV1). In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(70 citation statements)
references
References 35 publications
(102 reference statements)
4
66
0
Order By: Relevance
“…Discussion Specific protein-DNA-binding at equilibrium is often a deceptively simple, two-state process in which only the unbound reagents and the final complex are populated (4)(5)(6)(7)(8). However, the few kinetic mechanisms determined to date revealed a richer picture, with parallel routes and transient intermediates (4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion Specific protein-DNA-binding at equilibrium is often a deceptively simple, two-state process in which only the unbound reagents and the final complex are populated (4)(5)(6)(7)(8). However, the few kinetic mechanisms determined to date revealed a richer picture, with parallel routes and transient intermediates (4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
“…However, the few kinetic mechanisms determined to date revealed a richer picture, with parallel routes and transient intermediates (4)(5)(6)(7)(8). In the absence of high-resolution kinetic work, structural studies suggested that multistate routes for protein-DNA-binding start with the formation of nonspecific interactions with the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17), and that some dual-role residues may form transient nonnative interactions along the route (13-15, 17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some proteins diffuse mainly in 1D over long distances (2), whereas others favor a 3D pathway (3). Once at the target site, proteins without an enzymatic activity may bind to DNA along a single kinetic route (4)(5)(6)(7)(8)(9) or parallel routes (10,11). Each route may either be two-state (4-6, 10) or include populated kinetic intermediates (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Once at the target site, proteins without an enzymatic activity may bind to DNA along a single kinetic route (4)(5)(6)(7)(8)(9) or parallel routes (10,11). Each route may either be two-state (4-6, 10) or include populated kinetic intermediates (7)(8)(9)(10)(11). In the final consolidated complex, sequence recognition is mediated by specific contacts between protein residues and DNA bases (direct sequence readout) and by the conformational energetics of noncontacted bases (indirect sequence readout) (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%